Gestão da saúde: um estudo da estratégia saúde da família sob a ótica dos profissionais de saúde das Unidades Básicas de Saúde de Santarém - SOUSA, Fabiana Letícia Costa de (Universidade Federal do Oeste do Pará, 2024)
This research aims to understand health management in Basic Health Units in the city of Santarém, in addition to understanding its operation, services provided and the challenges that health professionals face for the implementation of such policies of Primary Health Care through the perspectives of the professionals who make up these UBS. Thus, the research was directed to the professionals who make up the Family Health Strategy, which is the main one in primary care. The discussion made it possible to understand the main challenges faced by health agents. In addition, it was evident the difficulties that the western region of Pará faces in its daily routine through rivers, lakes and forest. The results of such research point out problems in the management of the municipality and in the health units, since the lack of professionals and basic materials are common to the units.